Running periodization (part 4 - high school and college periodization) - Karp, J. (Techniques Magazine, 2023)
The high school and college cross-country and track environment presents a unique training problem. Between the emphasis on racing and the desire for immediate results, runners´ aerobic development is often sacrificed for the sake of intensity. And that´s not ideal if the goal is to become a better distance runner. Runners and coaches need to adequatly prepare for many races, sustain motivation and desire, and train with an optimal strategy.3